ANALISIS KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV SEKOLAH DASAR - Rindu Bintara, Devi Kelana; Perdana, Dayu Rika; Nuraini, Siti; Sowiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low critical thinking skills of fourth-grade students at SD Negeri X Metro Barat. This research aims to analyze the critical thinking abilities of fourth-grade elementary students based on six main sub-focuses: interpretation, analysis, evaluation, inference, explanation, and self-regulation. This study employed a qualitative method with a case study approach conducted at SD Negeri X Metro Barat. Data were collected through observations, interviews with the principal, teachers, and students, as well as document analysis, involving a total of nine informants. The findings indicate that students' critical thinking skills have developed but have not yet reached an optimal level. This study highlights the importance of habituation, the use of prompting questions, and systematic guidance from teachers to strengthen the critical thinking skills of elementary school students